2017
DOI: 10.1007/978-3-319-59111-7_31
|View full text |Cite
|
Sign up to set email alerts
|

Agile Methods in Ethiopia: An Empirical Study

Abstract: Abstract. This paper provides empirical evidence of agile method adoption in smaller companies in Ethiopia. Agile methods are emerging as best practice for software development in the global north. So, is there evidence that agile methods are being used in Ethiopia? A Grounded Theory approach was adopted using face-to-face interviews with 17 software professionals from 7 software companies, which were selected by using a snowball sampling technique. The interviews were semi-structured and open-ended and have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…Our findings are consistent with previous research conducted in Ethiopia, which show novice agile practitioners tend to mix plan-based and agile methods [18]. Also, companies experience gaps when implementing agile practices with missing roles, ceremonies and artefacts due to lack of staff, knowledge and finances.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with previous research conducted in Ethiopia, which show novice agile practitioners tend to mix plan-based and agile methods [18]. Also, companies experience gaps when implementing agile practices with missing roles, ceremonies and artefacts due to lack of staff, knowledge and finances.…”
Section: Discussionsupporting
confidence: 91%
“…Developing countries have been implementing agile methods in their software development process. Practitioners are aware of the benefits of agile and stress on the importance of its implementation [18]. Gaps between the developers and the end-users hinder the development process [3,10].…”
Section: Agile Implementation In Developing Countriesmentioning
confidence: 99%
“…Consequently, it is difficult to find a software development method that is most effectively adopted as it was originally suggested in textbook format [8]. Software organisations could further tailor agile methods in order to fit their country culture, values and strategies [20] [23].…”
Section: Tailoring Agile Methodsmentioning
confidence: 99%
“…Studies have investigated agile methods adoption in Kenya [15], Ethiopia [23] and Egypt [20]. Whereas, in Kenya where an offshore/onshore collaboration model was employed, in Ethiopia and Egypt, practitioners were adopting agile methods with little prior first hand experience.…”
Section: Agile Methods In Ict4dmentioning
confidence: 99%
“…Some research did focus on investigating software development challenges faced by practitioners in smaller software companies in specific regions e.g. sub-Saharan Africa where contributions were to literature in areas such as agile awareness and adoption challenges [8]. It was concluded that further research is required on how agile methodologies can be tailored for use in a developing country context.…”
Section: Related Workmentioning
confidence: 99%